Impact of glucocorticoids on the therapeutic efficacy of denosumab against osteoporosis in patients with rheumatoid arthritis - Jiwon Yang; Youngjae Park; Jennifer Jooha Lee; Seung-Ki Kwok; Ji Hyeon Ju; Wan-Uk Kim; Sung-Hwan Park (Therapeutic Advances in Musculoskeletal Disease)
Background: Rheumatoid arthritis (RA) and prolonged high-dose glucocorticoid (GC) treatment are established risk factors for osteoporosis. Objectives: In this study, we aimed to evaluate the therapeutic efficacy of denosumab according to the GC dose considered to increase the risk of glucocorticoid-induced osteoporosis (GIOP) in patients with RA. Design: A retrospective analysis of collected data on RA patients with osteoporosis starting denosumab. Methods: We included 418 patients with RA who were started on denosumab therapy and categorized them into those with and without GC intake ⩾2.5 mg/day for >3 months. The T -score and areal bone mineral density (aBMD) at the lumbar spine, total hip, and femur neck, as well as serum bone turnover markers, were measured at baseline and 12 months. We performed between-group and within-group comparisons of the BMD values at baseline and at 12 months. Results: Denosumab significantly increased the T -scores and aBMD at the lumbar spine, total hip, and femur neck after 12 months, regardless of GC intake. However, apart from the T -score at the lumbar spine, the other parameters did not show significant between-group differences. Similarly, in patients with anti-cyclic citrullinated peptide (CCP) antibody positivity or those treated with biologic or targeted synthetic disease-modifying antirheumatic drugs (DMARDs), although there were significant increases in the T -score and areal BMD at all sites in both groups, there were no significant between-group differences. Conclusion: Our findings suggest that the GC dose considered to increase the risk of GIOP did not significantly attenuate the therapeutic efficacy of denosumab in RA patients, including those positive for anti-CCP antibodies and users of biologic or targeted synthetic DMARDs.